Melatih Perkembangan Motorik Siswa Kelas II SD Inpres 07 Kampung Ambon Manokwari melalui Permainan Tradisional Tarik Tambang : Pengabdian - Irma Suriani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to observe the motor skills of 2nd grade elementary school children, through a tug-of-war game. This community service is a type of qualitative community service that includes observation of learning methods in an effort to develop children's motor skills through this type of game. Observation activities were carried out from March 3 to 10, 2025, which lasted for one week. In the initial stage, the author gave examples to children on how to play tug-of-war, then asked the children to imitate and repeat the examples that had been given. Based on the analysis of the results of observations for one week, it was found that student activity had increased significantly in carrying out regular motor activity learning, through explicit learning models and tug-of-war games. This increase was seen at every meeting, from Meeting I to Meeting IV. Meeting I was filled with observations of how teachers taught children. At Meeting II, the author introduced the rules of the tug-of-war game to the children. At Meeting III, the children's development was clearly visible, where most of the children understood the rules of the game, although there were still one or two children who were too active and broke the rules. Finally, at Meeting IV, this development was recorded as very good.